Identification of a cryptic IRF2BP2-RARA fusion in acute promyelocytic leukemia - Yin, C. Cameron (J Natl Compr Canc Netw, 2015)
Acute promyelocytic leukemia (APL) is characterized by fusion of RARA with PML, or rarely other gene partners. We report a patient with APL with a novel fusion between RARA and the interferon regulatory factor 2 binding protein 2 (IRF2BP2) genes. A 19-year-old woman presented with ecchymoses and epistaxis. Bone marrow examination showed morphologic and immunophenotypic features consistent with APL. PML oncogenic domain antibody was positive. Conventional cytogenetics, FISH, RT-PCR and oligonucleotide microarray for PML-RARA and common APL variant translocations were negative. Next generation RNAseq analysis followed by RT-PCR and direct sequencing revealed distinct breakpoints within IRF2BP2 exon 2 and RARA intron 2. The patient received ATRA, arsenic trioxide and gemtuzumab ozogamicin, and achieved complete molecular remission. However, the disease relapsed ten months later, two months after completion of consolidation therapy. This case expands the list of novel RARA partners identified in APL.